AI-POWERED FEEDBACK SYSTEMS IN WRITING SKILL DEVELOPMENT - Normo‘minova Charos Azimjonovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis explores the role of artificial intelligence (AI)-powered feedback systems in the development of writing skills among learners. The study highlights how AI tools provide real-time, personalized suggestions that help students improve grammar, structure, vocabulary, and writing style. It also discusses how such systems enhance learner confidence and motivation, ultimately contributing to more effective and independent writing practices.